Factors Influencing the Mechanical Characteristics of a Pile–Soil Interface in Clay Soil - Zhang, Mingyi; Sang, Songkui; Wang, Yonghong; Bai, Xiaoyu (Frontiers in Earth Science, 2020)
A series of direct shear tests using a large-scale constant-normal-stiffness direct-shear testing system was conducted to study the factors that influence the mechanical characteristics of a pile–soil interface in clay soil. Interfaces of different roughness (R = 0, 2, 4, and 6 mm) were tested in clay soil with four different water contents with four normal stresses under different shear rates during shearing. Results for the interfacial shear behavior are presented as shear-stress–shear-strain curves, shear strength, and parameters. The results show that (i) the higher the roughness, the higher the shear strength of the pile–soil interface.The larger the normal stress, the smaller the roughness effect on the shear strength and parameters of the pile-soil interface; and (ii) the higher the water content of the clay soil, the lower the shear strength of the pile–soil interface, with maximum cohesion at a water content of 25%. The main influence that increasing the water content has on the shear strength of the pile–soil interface is changing the coherence, while the shear rate in this test range has less effect on the shear strength of the pile–soil interface. Overall, the mechanical characteristics of the pile–soil interface are influenced by roughness, water content, and shear rate, and close attention should be paid to those three factors when analyzing test results.